Performance evaluation of dual mode dryer for in-shell cashew nuts - Balasubramanian, D.; Sandeep, T.N. (Journal of Plantation Crops, 2012)
Performance of a dual mode dryer developed to reduce the moisture content of in-shell cashew nut to improve its shelf life was evaluated. Dual mode dryer consisted of three major components viz., drying chamber, aspirator and heat exchanger. Its performance was evaluated by exposing in-shell cashew nuts at an average drying chamber temperature of 65 ºC for safe drying. Preliminary study on infusion of moisture into in-shell cashew nuts indicated that the moisture content of whole nuts and fractions viz., shell and kernel increased with increase in soaking period. Moisture reduction took place at faster rate in the case of electrical than thermal power which was used for the generation of heating media for drying moistened nuts. Average time required to reduce the moisture content of in-shell cashew nuts of small, medium and large size to safer level was worked out to be 4.41, 4.37 and 3.16 hrs in the case of electric power and 4.38, 4.28 and 4.11 hrs for thermal power respectively, indicating that the time taken for drying large size nuts was lesser than smaller size nuts. Drying rate among the size of the nuts varied mainly due to lesser nut count in a given mass for large size than small size nuts. Differential rate of drying was recorded for the nuts placed in different positions viz., top, middle and bottom of the drying chamber and it became non-significant after 4 hrs of drying. Drying of in-shell nuts followed falling rate period of drying and time required to reduce its moisture level from initial moisture content of 20.44 per cent to safer level of 8.00 per cent d.b was in the range of 2.84 to 4.51 hrs irrespective of source of power, size of the nuts and position of the tray. Energy required for desired moisture reduction was found to be in the range of 26.06 to 39.79 MJ for electrical system and 173.24 to 230.18 MJ in the case of cashew shell cake as biofuel.